Бледное пламя: Роман и рассказы / В. В. Набоков - Набоков Владимир Владимирович (Золотая коллекция, 1991)
Экземпляры: ф.4 (20170619) / Инвентарный номер: 038628 / Цена: 18.00 / Авт.знак: Н 14 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=Рус)6